The campaign value of incumbency: A new solution to the puzzle of less effective incumbent spending - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2008)
A puzzle in research on campaign spending is that while expenditure is positively related to votes won, this effect is far more strongly, or even exclusively, enjoyed by challengers rather than by incumbents. We unearth a new explanation for the puzzle, focusing on the hidden, yet variable, campaign value of office perquisites which incumbents deploy in their campaigns to win votes. When these variable office benefits are unobserved, then the effect is to make observed incumbent spending less effective than spending by challengers. Using data from the 2002 Irish general election, where incumbency was assigned a variable campaign value and included in declared campaign spending, we are able to demonstrate this hidden incumbency effect and estimate its relationship to electoral success, in terms of overall votes, share of votes, and probability of winning a seat. Contrary to previous research showing ineffective incumbent spending, we find that when the campaign value of office is also measured, public office value “spending” is not only very effective in winning votes, but also seems to be more effective than regular incumbent spending.